PENGARUH TEHNIK REBOZZO TERHADAP PENURUNAN NYERI PERSALINAN DI KLINIK ERDONA BATUGURU DESA PANCOWARNO KEC. SALAPIAN TAHUN 2021 - Eka Sri Wahyuni; Mutiara Dwi Yanti; Septa Dwi Insani (JURNAL ILMIAH DHDT - KEBIDANAN, 2021)
Labor pain is a physiological process that is felt by every mother during childbirth. Pain that is not managed properly will have an impact on the labor process. The degree of pain varies, including mild, moderate and severe. The Rebozzo technique is one of the non-pharmacological methods that can be used to reduce labor pain. This study aims to determine whether there is a decrease in labor pain with the rebozzo technique. This research was conducted from April to May 2021 at the Erdona Batuguru Clinic, Pancowarno Village, Salapian District, Langkat Regency. This research method uses a quasi-experimental research design with a pre-test-post-test design with a control group, using a non-probability sampling technique, namely purposive sampling with the Federer formula with a sample of 16 people. The results of the Paired Sample t-Test also obtained a significant value, namely 0.001 (<0.005). So that Ho is rejected and Ha is accepted, this shows that there is a difference in the level of pain before and after the Rebozzo technique. This means that the rebozzo technique can reduce labor pain.